1977
DOI: 10.3758/bf03214076
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-induced polydipsia contrast in the rat

Abstract: Schedule-induced polydipsia was studied using a behavioral contrast paradigm. Food pellets were delivered to food-deprived rats on a response-independent FT l-min sehedule. Licking on a tube produeed water on a MULT FR 10 FR 10, MULT FR 10 EXT, or MIXED FR 10 EXT for three rats (Experiment 1) and on a MULT VI VI, MULT VI EXT, or MIXED VI EXT sehedule for three other rats (Experiment 2). On the FR sehedules, rats eould drink more water by inereasing lick rates, but on the VI schedules the amount of drinking was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Results demonstrated that the relative time spent drinking in each component varied according to the matching law (Herrnstein, 1970). In both the Porter and Allen (1977) and Cohen (1975) experiments, adjunctive licking behavior exhibited schedule interactions common to those seen with operant behavior, and thus supported the hypothesis that operant and adjunction behaviors are similar. Recently, however, Hamm, Porter, and Oster (1978) failed to observe summation (see Weiss, 1972) of adjunctive licking under conditions that pro-93 1981, 36., [93][94][95][96][97][98][99] duced summation of operant barpressing.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Results demonstrated that the relative time spent drinking in each component varied according to the matching law (Herrnstein, 1970). In both the Porter and Allen (1977) and Cohen (1975) experiments, adjunctive licking behavior exhibited schedule interactions common to those seen with operant behavior, and thus supported the hypothesis that operant and adjunction behaviors are similar. Recently, however, Hamm, Porter, and Oster (1978) failed to observe summation (see Weiss, 1972) of adjunctive licking under conditions that pro-93 1981, 36., [93][94][95][96][97][98][99] duced summation of operant barpressing.…”
supporting
confidence: 55%
“…Another research interest has focused on the similarities or differences between adjunctive (interim responses) and operant (terminal responses) behavior. For example, Porter and Allen (1977) delivered food pellets on a fixed-time schedule in order to induce an adjunctive licking response. The availability of water was then placed on various multiple schedules, and behavioral contrast (Reynolds, 1961) of adjunctive licking was observed.…”
mentioning
confidence: 99%
“…This phenomenon has since been confirmed in other species, e.g. mice (Palfai, Kutscher & Symons, 1971); guinea-pigs (Porter, Sozer & Moeschl, 1977); gerbil (Porter & B.ryant, 1978); monkey (Allen &Kenshalo, 1976 andBarrett, Stanley &Weinberg, 1978); pigeon (Magyar & Malagodi, 1980) and pig (Ingram, Sharman & Stephens, 1981).…”
Section: Introductionmentioning
confidence: 84%
“…The interbout interval is jointly determined by the scheduled interpellet interval, which fixes the minimal interval between drinking occasions, and the proportion of intervals in which a bout is actually initiated. Since previous research has shown that increases in interbout interval, whether produced directly by removing access to the water tube during interpellet intervals (Allen and Porter, 1976;Porter and Allen, 1977), or indirectly by stretching the interpellet interval (Allen, Porter and Arazie, 1975), result in increases in bout size, it is plausible that the obtained interbout interval is a more direct determinant of bout size than is the interpellet interval. If so, expressing the milliliter-per-bout functions in Figure 1 in terms of the interbout interval should improve the orderliness of the plotted functions.…”
Section: Discussionmentioning
confidence: 99%